Deutsche und albanische Phraseologismen mit Tierbezeichnungen im Kontrast - Sadiku, Milote (Linguistik Online, 2011)
The object of this article are animal idioms in contemporary German and Albanian: the article treats those units that denote animal names in their formal structure with phraseological, figurative meaning. The aim of the article is to identify and describe the differences and similarities between these two languages from the viewpoint of a contrastive analysis. The German phraseology has often been the subject of inter-linguistic comparisons. However, this can not be claimed for the German – Albanian language analysis. In this article, some similarities and differences in animal symbolism in the German and Albanian phraseology are illustrated by typical examples, and equivalence relations between the German and Albanian animal idioms are identified.It can be concluded that the animal names in idiom units indicate positive and negative characteristics or behavior of people. One result is that the negative semantic characteristics predominate in both languages. The animal name depends on a concrete idiom not only from the ideas and values that are attributed to an animal in a language community, but also from the already existing structures and pragmatic rules in a concrete language.